Sleep regularity in athletes: comparing sex, competitive level and sport type - Mello, M. T.; Facundo, L. A.; Brant, V. M.; Guerreiro, R. C.; Andrade, H. A.; Louzadda, F. M.; Silva, A. (29th Annual Congress of the European College of Sport Science, 2-5 July 2024, Book of Abstracts, 2024)
INTRODUCTION: This study aims to describe the athletes` sleep regularity using the Sleep Regularity Index (SRI) and determine whether factors, such as sex, competitive level and sport type, could affect the sleep/ wake rhythm. METHODS: It is a descriptive, cross-sectional study consisting of 172 athletes (25 ± 7 y old; 45 women). Seventy-three competed in team sports and 99 in individual sports. Furthermore, 56 competed in the international level, 95 in the national and 21 in the regional. We recorded the SRI values for at least 5 d via continuous actigraphy. RESULTS: We recorded a mean SRI value of 73 ± 12. We found no significant differences between athletes` sleep parameters in relation to sleep regularity. Furthermore, SRI data showed no correlations (Spearman`s *) with sleep parameters, bed time and wake time. Female athletes (p = 0.001) and individual sport athletes (p = 0.001) reported better sleep regularity than their counterparts. International-level athletes reported better sleep regularity than those in other competitive levels (national: p = 0.001; regional: p = 0.024). CONCLUSION: Our study showed that international level athletes, female athletes and individual sport athletes reported better sleep regularity. Additionally, SRI data showed no correlation with athletes` sleep parameters, bed and wake time. In conclusion, we observed better sleep regularity para-meters in female athletes, international-level athletes and individual sport athletes. Additionally, the SRI showed no correlations with the athletes` sleep parameters, BT and WT. Our results also showed that athletes have inade-quate sleep duration for their specific goals. Acknowledgements: This study is supported by Fundação de Amparo à Pesquisa do Estado de Minas Gerais (FAPEMIG), Conselho Nacional de Desenvolvimento Científico e Tecnológio (CNPq), Coordenação de Aperfeiçoamento de Pessoal de Nível Superior (CAPES), Centro de Estudos em Psicobiologia e Exercício (CEPE), Centro Multidisciplinar em Sonolência e Acidentes (CEMSA), Pro - Reitoria de Pesquisa (PRPq) - UFMG - Universidade Federal de Minas Gerais, Fundação de Apoio ao Ensino, Pesquisa e Extensão (FEPE/UFMG), Centro de Treinamento Esportivo (CTE/EEFFTO/UFMG, Ministério da Cidadania do Governo Federal (Brasília, Brazil - Protocol Numbers: 58000.008978/2018 - 37 and number: 71000.056251/2020 - 49), Comitê Olímpico Brasileiro (COB), Academia Paralímpica Brasileira do Comitê Paralímpico Brasileiro (APB/CPB) and Instituto Tecnológico Vale (ITV).